Antimicrobial Immune Response - del Mar Ortega-Villaizan, Maria; Chico, Veronica (IntechOpen, 2021)
Infectious microbial agents such as viruses, bacteria, fungi, and parasites can cause pathological disorders and even death in organisms exposed to the environment. However, organisms have an immune system to control infection caused by pathogens. The immune system is divided into the innate and the adaptive immune systems. The innate immune system is the first mechanism to respond to infections, whereas the adaptive immune system is based on immune memory. This book provides an overview of antiviral and antibacterial immune responses in different immune-reactive organs and across different animal species, from higher to lower vertebrates.